Preparation and characterization of poly(amidoxime) chelating resin from polyacrylonitrile grafted sago starch - Lutfor, M.R.; Silong, Sidik; Md Zin, Wan; Ab Rahman, M.Z.; Ahmad, Mansor; Haron, Jelas (Elsevier Science, 2000)
The preparation of a chelating ion-exchange resin containing amidoxime functional group was carried out by polyacrylonitrile (PAN) grafted sago starch. The PAN grafted copolymer was obtained by free-radical initiating process using ceric ammonium nitrate as an initiator. Conversion of nitrile groups of the grafted copolymer into the amidoxime was carried out by treatment with hydroxylamine under alkaline solution. The chelating poly(amidoxime) resin was characterized by FT-IR spectra, TG and DSC analyses. The chelating behavior of the prepared resin was carried out by using some metal ions. A significant binding property of metal ions by the chelating resin was observed and the maximum copper capacity was 3.0 mmol g-1 at pH 6. The sorption capacities of metal ions by the resin were pH-dependent, and its selectivity towards these metals ions is in the following order: Cu2+ > Fe3+ > As3+ > Zn2+ > Ni2+ > Cd2+ > Co2+ > Cr3+ > Pb2+. The rate of exchange was rapid, i.e. t1/2 < 9 min, based on the exchange of copper ion.